Life roles in transition - Šverko, Branimir (Array, 2001)
Compared changes in life values in communist and postcommunist Croatia. 1, 321 university students and adult workers residing in Croatia completed questionnaires in 1983 or 1998 concerning their role participation, role commitment, and value expectations concerning their work, study, home and family, community service, and leisure environments. Results show that the importance of the working role increased for university Ss, while interest in studying decreased. As well, the importance of home and family, and community service increased, as did role participation in and commitment to work. Among adult working Ss, there was a dramatic decrease in the participation, commitment, and value expectations concerning community service.